2011
DOI: 10.1088/1751-8113/44/41/415304
|View full text |Cite
|
Sign up to set email alerts
|

Quantum discord of two-qubit rank-2 states

Abstract: Abstract. Among various definitions of quantum correlations, quantum discord has attracted considerable attention. The connection between the quantum discord and the entanglement of formation is described by Koashi-Winter relation. We investigate this relation from the viewpoint of the quantum channel that is isomorphic to the given state. It is shown that in the case of two-qubit states the channel, on the one hand, determines the form of the quantum steering ellipsoid of the given state, and on the other han… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 48 publications
1
74
0
1
Order By: Relevance
“…The steering ellipsoid formalism [11][12][13][14] gives a faithful representation of two-qubit states analogous to the Bloch vector picture for a single qubit. Any two-qubit state may be represented by an ellipsoid inside the Bloch sphere, but not all ellipsoids inside the Bloch sphere represent a two-qubit state.…”
Section: Introductionmentioning
confidence: 99%
“…The steering ellipsoid formalism [11][12][13][14] gives a faithful representation of two-qubit states analogous to the Bloch vector picture for a single qubit. Any two-qubit state may be represented by an ellipsoid inside the Bloch sphere, but not all ellipsoids inside the Bloch sphere represent a two-qubit state.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum discord for a Bell-diagonal state was analytically obtained [10]. Much research has had a focus on finding the quantum discord of the X state [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Shi et. al [16,17] showed that there are some quantum states where 3 element POVM should be used for optimal quantum discord. The optimality for 3 element POVM can be found by a triangle formed by the direction vectors.…”
Section: Introductionmentioning
confidence: 99%
“…Applying the map Ω Ω Ω to the classical state σ c = 1 2 (|0 0| ⊗ |0 0| + |1 1| ⊗ |1 1|) leads to ρ = 1 2 (|0 0| ⊗ |0 0| + |1 1| ⊗ |+ +|), which has non-zero discord [34], but vanishing entanglement since it is a convex combination of product states. Given that Ω Ω Ω B (ρ) possesses diagonal elements which are independent of the off-diagonal elements of ρ it has zero distinguishing power for any input state.…”
Section: In Other Words If W (θ θ θmentioning
confidence: 99%